Chrono-optimizing vaccine administration: a systematic review and meta-analysis - Vink, Koen; Kusters, Johannes; Wallinga, Jacco (Frontiers in Public Health, 2025)
BackgroundIncreasing evidence suggests that vaccine responses may vary based on the time of day of administration. This systematic review provides a comprehensive overview of the impact of vaccination timing on immune responses, to assess its potential role in optimizing vaccination programs.MethodsA systematic literature search was performed in Embase, Medline and Scopus to identify eligible observational studies and clinical trials that assessed immune responses following vaccination at different times of the day in humans. A meta-analysis of clinical trials was conducted to quantify the effect size of vaccination timing on antibody responses.ResultsThe search identified 17 studies that compared vaccine responses at different times of the day, covering vaccinations against COVID-19 (9), influenza (5), hepatitis B (2), hepatitis A (1), and pneumococcal infection (1). Eleven out of these 17 studies demonstrated statistically significant effects of vaccination timing on the antibody response, with 10 reporting stronger antibody responses following morning compared to afternoon vaccination. Of the six subgroups with an average age of 60 years and older, five showed significantly stronger antibody responses following morning vaccination, while the sixth showed a significant effect only in men. In contrast, only five out of 16 subgroups with an average age younger than 60 years showed a statistically significant effect of vaccination timing on antibody titers. Similarly, the meta-analysis indicated that receiving influenza vaccination in the morning elicited a stronger antibody response than in the afternoon (SMD = 0.24, 95% CI = 0.01–0.47), with subgroup analyses revealing a larger effect in adults aged 65 and older (SMD = 0.32, 95% CI = 0.21–0.43) compared to those aged 60 or younger (SMD = 0.00, 95% CI = −0.17–0.17).ConclusionMorning vaccination enhanced antibody responses in adults aged 60 years and older, a key demographic for influenza and COVID-19 vaccination. Chrono-optimizing vaccine administration may offer a low-risk, low-cost strategy to boost vaccine effectiveness in this age group.Systematic review registrationhttps://inplasy.com/inplasy-2025-1-0060/.